Sebastián Fox Morcillo, De honore, Estudio y traducción de Antonio Espigares Pinilla, Ediciones Complutense (“Serie Investigación”), Madrid 2017, pp. 137, ISBN 978-84-669-3521-0 - Curnis, Michele (ΠΗΓΗ/FONS, 2019)
–